Optical characterization of colloidal zinc selenide quantum dots prepared through hydrothermal method - Fakhrurrazi Ashari,; Liew, Josephine Ying Chyi; Zainal Abidin Talib,; W. Wahmood Wan Yunus,; Leong, Yong Jian; Lee, Han Kee; Chang, Fu Dee; Burhanuddin Yeop Majlis, (Penerbit Universiti Kebangsaan Malaysia, 2016)
Zinc selenide (ZnSe) quantum dots (QDs) have been synthesized through a hydrothermal method using ZnCl2 and Na2SeO3 powder as the precursor in the presence of oleylamine as capping agent. The hydrothermal route was conducted at a moderate temperature (150°C) for 8 h. Optical properties of ZnSe QDs were studied through ultraviolet-visible spectroscopy (UV-Vis) and photoluminescence (PL) while the structural properties of ZnSe QDs were characterized using transmission electron microscope (TEM). The photoluminescence (PL) characterization on ZnSe QDs showed that the QDs emit light in blue range region at around 440 nm with optical band gap energy at 3.68 eV. The TEM results showed that the average particle size is around 8.9 nm. It is a good candidates for optoelectronic devices such as light emitting diodes (LED).